Epidemiology of scorpionism in France: nationwide scorpion exposure. (3rd October 2021) - Vaucel, Jules-Antoine; Gil-Jardine, Cédric; Labadie, Magali; Larréché, Sébastien; Paradis, Camille; Nardon, Audrey; Courtois, Arnaud; Langrand, Jérôme; Kallel, Hatem
Abstract: Introduction: In France, 57 species of scorpions are described with a limited number of clinical studies. In this article, we report the epidemiology of scorpion sting events in mainland France and its overseas territories based on cases reported to the French poison-control centres (FPCC). Material and method: This retrospective multicentre study was conducted with data from FPCC's files about scorpion stings between January 1, 2011 and December 31, 2020. Result: Among 975 recorded files, 624 patients were included because they were stung by scorpions native to French territories. Most stings occurred along the Mediterranean coast in summer and indoors (in persons' homes) during the daytime. The scorpions were identified in 50% of cases. According to signs of envenoming, patients were divided into class III (2 cases; 1%), class II (51 cases; 8%), class I (444 cases; 71%) and asymptomatic stings (127 cases; 20%). Twelve pregnant women were stung and two of them had contractions, which triggered childbirth in one woman. Ten patients had local infections in the first week after the sting. One patient had venous thrombosis 2 days after the sting. Life-threatening scorpions, i.e., Tityus obscurus, Tityus sylvestris and Centruroides pococki, in French territories are limited to French Guiana and Lesser Antilles. Class II envenoming cases are recorded for Buthus occitanus, Euscorpius spp. in mainland France, and Isometrus maculatus in French Guiana, the Lesser Antilles (Guadeloupe and Martinique) and territories in the Indian Ocean (Mayotte and Réunion Island) and Pacific Ocean (French Polynesia). Only cases of local manifestation was reported for Belisarius xambeui in mainland France. Conclusion: Scorpion stings in French territories are frequently on the Mediterranean coast and French Guiana. Life-threatening cases are limited to T. obscurus, T. sylvestris and Centruroides pococki stings in French Guiana and Lesser Antilles.